Evaluation of the Acute Flaccid Paralysis Virological Surveillance System in Polio-Free Morocco, 2010-2018 - Sanae Lemrabet; Maria El Qazoui; Lalla Meryem Idrissi Azzouzi; Ahmed Rguig; Malika Elhamdaoui; Abdelkarim Filali-Maltouf; Leila Medraoui; Hicham Oumzil (Hindawi Limited, 2022)
Background. The goal of Acute flaccid paralysis (AFP) surveillance is to comprehensively investigate and report any case of a child below 15 years with a floppy weakness. This is essential for the poliovirus eradication initiative. Objective. In this study, we analyzed the results of nine-year surveillance (2010-2018) of AFP in Morocco. Method. This was a descriptive, retrospective study of cases with AFP routinely documented at the National Referral Laboratory of Polio (NRLP) from 2010 to 2018. Results. Among the 884 AFP cases identified and analyzed, we identified 11 polioviruses as Sabin-like vaccine strains (PSL). PSL were isolated in 11 samples of AFP cases received at the laboratory, including one PSL1, three PSL2 + PSL3, one PSL1 + PSL2, and one PSL1 + 2 + 3. The annualized nonpolio AFP rate per 100,000 children under 15 years ranged from 0.84 during 2011-2015 to 2.29 in 2018. The stool adequacy indicator was poor and may be improved with better delivery times and maintaining the cold chain. The incidence of isolated nonpolio enteroviruses (NPEV) varied between 2.27% and 12.6%, with the average not exceeding 6.35%; the incidence remained low compared to the indicator set by the World Health Organization (WHO). Conclusion. Morocco was certified polio-free by WHO in 2015, and since then no cases of wild poliovirus have been reported. Overall, although the nonpolio AFP rate has risen to the WHO standard, stool adequacy and the proportion of nonpolio enteroviruses need to be improved. The laboratory can adopt alternative techniques, independent of cell culture, to ensure that imported cases of poliovirus are not missed, especially in this era of eradication.